2020
DOI: 10.1128/jvi.01006-20
|View full text |Cite|
|
Sign up to set email alerts
|

Next-Generation Porcine Intestinal Organoids: an Apical-Out Organoid Model for Swine Enteric Virus Infection and Immune Response Investigations

Abstract: The intestinal organoid culture system is a pathbreaking working model for investigating pathogen-host interactions in the intestines. However, due to the limitations of the first generation of intestinal organoids, basal-out structure and growth in Matrigel, most pathogens can rarely attach to the apical membrane directly and hardly initiate infection. In this study, we first developed a next-generation porcine intestinal organoid culture system, characterized by an apical membrane on the surface, called apic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(105 citation statements)
references
References 18 publications
6
99
0
Order By: Relevance
“…A recent study showed that human enteroid cell polarity can be reversed by removal of the extracellular matrix [ 33 ]. The method developed by Co et al was applied to reverse epithelial polarity in pig jejunum enteroids in suspension cultures [ 34 ]. However, in this study, the polarity failed to be reversed in ~20% organoids after 3 days, which indicates phenotypic variability in these culture conditions.…”
Section: Phenotype Of Livestock Intestinal Organoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that human enteroid cell polarity can be reversed by removal of the extracellular matrix [ 33 ]. The method developed by Co et al was applied to reverse epithelial polarity in pig jejunum enteroids in suspension cultures [ 34 ]. However, in this study, the polarity failed to be reversed in ~20% organoids after 3 days, which indicates phenotypic variability in these culture conditions.…”
Section: Phenotype Of Livestock Intestinal Organoidsmentioning
confidence: 99%
“…Livestock intestinal organoids were successfully infected by a variety of enteric pathogens. Pig intestinal organoids were infected by several swine coronaviruses (porcine epidemic diarrhea virus (PEDV), transmissible gastroenteritis virus (TGEV) and porcine deltacoronavirus (PDCoV)) [ 21 , 29 , 34 , 38 ], by the bacteria Salmonella Typhimurium [ 20 ] and Lawsonia intracellularis [ 36 ] and by the protozoan parasite Toxoplasma gondii [ 20 ]. Bovine intestinal organoids were infected by Salmonella Typhimurium , Toxoplasma gondii and by group A rotaviruses [ 20 , 24 ].…”
Section: Host-microbe Interactions In Livestock Intestinal Organoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal organoids can also be maintained in suspension culture, where the cells switch their polarity so that the apical membrane faces outwards; this has already been achieved with crypts isolated from the porcine colon and jejunum. 71,78 This technique permits easier access to the apical surface of the epithelium and increases the available surface area, while keeping the cells in a proliferative state. Figure 3 illustrates a range of different methods used for the propagation of intestinal organoids.…”
Section: Culture Techniques Of Intestinal Organoid Modelsmentioning
confidence: 99%
“…Successful infection of this ‘next-generation’ model with a swine enteric virus was confirmed, as well as the elicitation of antiviral inflammatory responses. 71…”
Section: Potential Applications For Intestinal Organoid Modelsmentioning
confidence: 99%